Pengaruh Kualitas Ruang Terbuka Hijau terhadap Respon Urban Stress Pengunjung Taman di Provinsi DKI Jakarta - Prasetio, Hamyah; Syarief, Azhari (Al-DYAS, 2024)
Green open space is an important component in cities that can provide benefits in reducing the negative effects of urban stress. This is an important aspect for the City of Jakarta to reduce the effects of urban stress by improving the quality of green open spaces represented by satisfying parks. The objectives of this research are (1) Knowing the correlation relationship urban stressor to the response urban stress park visitors. (2) Knowing the influence of the quality of green open space on the response urban stress. (3) Determine priorities for developing green open spaces. This research method uses a quantitative approach by taking park samples using proportional sampling with a total sample of 22 parks and a sample of respondents using the linear time function method with a total of 330 park visitors. Data were collected using a questionnaire which was analyzed using the importance performance analysis method and multiple linear regression analysis which was processed using IBM SPSS Statistics 25. To determine priorities for developing green open spaces using spatial analysis using vegetation density, comfort index, and population density which was done by overlapping scoring. (overlay) with ArcGIS 10.8 software. The results of this research found that there was a correlation between several urban stressor variables and the urban stress response variable with a significance value of <0.05 with the highest correlation in the sufficient category, which indicates that the higher the urban stressor, the emotional response and behavioral response will increase. This research shows that there is an influence between the park satisfaction variable on the urban stress response variable with the following regression equation: (1) Ycognitive = 7.462 + 0.044 X1(uses & Activities) + 0.042 X4(Sociability); (2) Yemotion = 13.558 + 0.053 X1(uses & Activities) + 0.040 X2(Access & Linkages) + 0.036 and (3) Ybehavior = 10.010 + 0.041 X4(Sociability) + 0.035 X1(uses & Activities) + 0.031 X3(comfort & image). From the results of the spatial analysis, the highest category area is 52,510.69 ha, which is the second priority for developing green open space.